Non-linear static and cyclic analysis of steel frames with semi-rigid connections - Chan, S. L.
This book is devoted to the discussion and studies of simple and efficient numerical procedures for large deflection and elasto-plastic analysis of steel frames under static and dynamic loading. In chapter 1, the basic fundamental behaviour and philosophy for design of structural steel is discussed, emphasising different modes of buckling and the inter-relationship between different types of analysis. In addition to this, different levels of refinement for non-linear analysis are described. An introduction is also given to the well-known P- & dgr; and P- & Dgr; effects. Chapter 2 presents the basi.